2016
DOI: 10.1093/jjco/hyw168
|View full text |Cite
|
Sign up to set email alerts
|

Advancements of liver transplantation for hepatocellular carcinoma in Korea

Abstract: The Milan criteria are still considered the gold standard for patient selection criteria for liver transplantation in patients with hepatocellular carcinoma. However, those criteria may be too strict and thus exclude a significant number of patients who could benefit from liver transplantation. Based on this notion, many expanded selection criteria have been suggested. In Asian countries, where there is a serious shortage of deceased donor organs, living donor liver transplantation accounts for the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…In addition to liver resection, LT has become a definitive treatment for HCC, with studies reporting better long-term overall survival and disease-free survival with LT than with liver resection [ 14 ]. Moreover, criteria for LT have expanded [ 15 ]. Extrahepatic recurrence after LT is the most frequent cause of patient mortality, with the lungs being one of the most common sites of extrahepatic metastases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to liver resection, LT has become a definitive treatment for HCC, with studies reporting better long-term overall survival and disease-free survival with LT than with liver resection [ 14 ]. Moreover, criteria for LT have expanded [ 15 ]. Extrahepatic recurrence after LT is the most frequent cause of patient mortality, with the lungs being one of the most common sites of extrahepatic metastases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, most expanded criteria that have been suggested for DDLT showed longterm survival rates of >70%, not significantly inferior to those under the MC . However, LDLT differs from DDLT in that because LDLT is performed based on private relationships between the donor and the recipient, liver grafts are dedicated to only 1 potential recipient . Expanding the LDLT criteria for HCC would not result in decreased LT opportunities for patients with other etiologies, and thus, slightly lower expected survival could be acceptable in LDLT .…”
Section: Discussionmentioning
confidence: 99%
“…In their first study, they found that their patients with HCCs that met the MC had a 75% overall survival rate and an 83% recurrence‐free survival rate 4 years after LT . The MC justified LT for HCC by improving the longterm results to levels comparable with those of LT for nonmalignant diseases . Thus, the MC is undoubtedly the standard of choice for patient selection for LT for HCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some liver transplant programs switch their immunosuppression protocol from tacrolimus to rapamycin in patients with high risk for HCC recurrence after transplantation. However and on retrospective studies, its effect on long term overall survival on patients after liver transplantation for HCC, have had conflicting results [39,40].…”
Section: Signaling Of Energy Expenditure and Metabolismmentioning
confidence: 99%